2019
DOI: 10.1111/acel.13011
|View full text |Cite
|
Sign up to set email alerts
|

Late‐onset retinal degeneration pathology due to mutations in CTRP5 is mediated through HTRA1

Abstract: Late‐onset retinal degeneration (L‐ORD) is an autosomal dominant macular degeneration characterized by the formation of sub‐retinal pigment epithelium (RPE) deposits and neuroretinal atrophy. L‐ORD results from mutations in the C1q‐tumor necrosis factor‐5 protein (CTRP5), encoded by the CTRP5/C1QTNF5 gene. To understand the mechanism underlying L‐ORD pathology, we used a human cDNA library yeast two‐hybrid screen to identify interacting partners of CTRP5. Additionally, we analyzed the Bruch's membrane/choroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 72 publications
(94 reference statements)
1
20
0
Order By: Relevance
“…45,54,76 Some mouse strains exhibit thin BLamD, and, to date, only models involving the genes listed above have thick BLamD. 66,77 Aged monkeys may naturally exhibit soft drusen, but lack BLamD and do not progress to atrophy or NV, 78 suggesting that BLamD is required for drusen that progress. Indeed, BLamD may share some of the pathophysiology postulated for drusen, with important differences.…”
Section: Discussionmentioning
confidence: 99%
“…45,54,76 Some mouse strains exhibit thin BLamD, and, to date, only models involving the genes listed above have thick BLamD. 66,77 Aged monkeys may naturally exhibit soft drusen, but lack BLamD and do not progress to atrophy or NV, 78 suggesting that BLamD is required for drusen that progress. Indeed, BLamD may share some of the pathophysiology postulated for drusen, with important differences.…”
Section: Discussionmentioning
confidence: 99%
“…The C1QTNF5 gene product is present in the lateral and basal membrane of retinal pigment epithelial cells and the ciliary body [ 42 ]. It interacts with HTRA1 in mice and affects extracellular matrix turnover, which might explain the development of subretinal deposits in LORD [ 43 , 44 , 45 ]. Following the resolution of X-ray structures of the globular domain of C1QTNF5 [ 16 , 18 ], molecular models were built to explain the mechanism of C1QTNF5-mediated cell adhesion among RPE cells and RPE-Bruch membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact disease mechanisms are not clear, studies in human postmortem samples and animal models of these inherited macular degenerations have demonstrated that either the proteins themselves, or ECM components modulated by the proteins, aggregate in the BM. [30][31][32] To date, no clinical biomarkers describing the primary pathology underlying these conditions have been reported.…”
Section: Discussionmentioning
confidence: 99%